2019
DOI: 10.14444/6035
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated With Failure to Reach Minimal Clinically Important Difference in Patient-Reported Outcomes Following Anterior Cervical Discectomy and Fusion

Abstract: Background: The minimum clinically importance difference (MCID) represents a threshold for improvements in patient-reported outcomes (PROs) that patients deem important. No previous study has comprehensively examined risk factors for failure to achieve MCID after anterior cervical discectomy and fusion (ACDF) procedures for radiculopathic symptomatology. The purpose of this study is to determine risk factors for failure to reach MCID for Neck Disability Index (NDI), Visual Analog Scale (VAS) neck pain, and VAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 31 publications
4
8
0
Order By: Relevance
“…The present study could not find that high age was a predictor of non-success in neither neck disability nor arm pain. This is supported by other multivariate studies [ 2 , 29 , 34 ]. Further, both comorbidity and ASA level only came out as significant predictors for non-success in the present univariate analyses but not in the final multivariate analysis.…”
Section: Discussionsupporting
confidence: 88%
“…The present study could not find that high age was a predictor of non-success in neither neck disability nor arm pain. This is supported by other multivariate studies [ 2 , 29 , 34 ]. Further, both comorbidity and ASA level only came out as significant predictors for non-success in the present univariate analyses but not in the final multivariate analysis.…”
Section: Discussionsupporting
confidence: 88%
“…Khalid et al also found that upper cervical spine surgeries were at increased risk for postoperative dysphagia 31 . Longer operative times, as previously shown by Narain et al 27 , were significantly associated with a postoperative complication. ENT surgeon-assisted cases were more likely to have a postoperative complication.…”
Section: Discussionsupporting
confidence: 70%
“…10 Moreover, investigators have reported that higher comorbidity burdens act as negative predictive factors for achieving an MCID for disability and physical function scores among ACDF and lumbar decompressions patients, respectively. 5,11 While numerous studies report on how multiple comorbidities increase the risk of complications, 12,13 few focus on the cervical spine and even fewer investigate the effects on physical function. Although traditionally more attention has been placed on outcomes in the lumbar spine, cervical spine conditions have distinct etiologies and symptoms, such as myelopathic or radicular arm pain, that can translate into differences in outcomes.…”
Section: Introductionmentioning
confidence: 99%